Preparation method of steam-cured concrete prefabricated component
By pre-soaking and spraying the regenerated aggregate and water slag sand, and laying pre-wet cotton gauze in the concrete for steam curing and carbonization curing, the low late-stage concrete strength and poor durability caused by steam curing are solved. The problem is to achieve the effect of improving the later strength and durability of concrete.
Patent Information
- Application Number
- CN202411779284.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-21
AI Technical Summary
Steam curing leads to the increase in the early strength of concrete but the lower strength in the later stage, poor durability, and greater brittleness during lifting and transportation.
By pre-soaking the regenerated aggregate and water residue sand, spraying the inorganic salt solution or sodium dodecyl benzenesulfonate solution containing Mg2+, Al3+, Fe3+; laying pre-wet cotton gauze in concrete and steam maintenance , carbonization and curing to reduce the amount of calcium hydroxide formation and improve its morphology.
It improves the late strength and durability of steamed concrete, reduces brittleness, and enhances the overall performance of concrete.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steam-cured concrete prefabricated components, and in particular to a method for preparing a steam-cured concrete prefabricated component. Background Art
[0002] Steam curing can quickly improve the early strength of concrete and meet the strength requirements for demolding and lifting of prefabricated components, thereby accelerating mold turnover and improving factory efficiency. However, steam curing can also cause the concrete to have lower strength in the later stage, worse durability than standard cured concrete, and greater brittleness during lifting and transportation. The main reasons for this phenomenon are: 1) The rapid hydration process of cement-based materials in the early stage causes uneven distribution of hydration products and many tiny cracks inside the concrete; 2) The early formation of more hydration products tightly wraps the unhydrated cement particles, isolating the contact between water and unhydrated cement particles, causing the concrete to be dry and lack of water, preventing the later hydration of cement particles; 3) Under steam curing conditions, more crystalline hydration products are formed, such as calcium hydroxide, which is enriched and grows around the aggregate, and the amount formed is higher than that under standard curing conditions, which reduces the gelling properties of cement-based materials and is not conducive to the durability of concrete.
[0003] To solve the above problems, the main solutions in the current patent include: CN201210381195.X proposed a calcium hydroxide crystallization inhibitor and an ettringite crystallization inhibitor. The crystallization inhibitor is used to soak or spray concrete coarse aggregate, which can effectively improve the durability of steam-cured concrete.
[0004] CN202111238423.3 By applying weak acid on the surface of aggregate, weak acid treatment of aggregate will reduce the pH value of the aggregate surface. The low-density distributed calcium hydroxide enriched and grown on the aggregate surface under steam-curing conditions will be consumed by the lower pH value or weak acid, thereby improving the density of the interface between the cement slurry and the aggregate. However, since the water absorption rate of the aggregate surface, especially the coarse aggregate, is low, the amount of crystallization inhibitor and weak acid applied on the surface is limited, and therefore the consumption of calcium hydroxide is also relatively limited.
[0005] CN202210293569.6 By setting up porous steel pipes, during steam curing, steam can be transmitted to the interior of the concrete component through the steel pipes, and at the same time, heat conduction through the metal fibers inside the concrete ensures uniform heating of all parts of the precast concrete; in addition, the presence of porous steel pipes and porous fiber pipes also provides a channel for water replenishment of precast concrete components. However, the amount of reinforcement in concrete is limited. In order to ensure the contribution of steel bars to the structural bearing capacity, the amount of porous steel pipes used to replace steel bars is also very limited; at the same time, the dispersion problem of porous fiber tubes also brings new problems to concrete.
[0006] CN201510513444.X A highly active composite admixture for steam-cured concrete products, the composition of which is as follows: anhydrite: silica powder: fly ash: ground slag powder in a ratio of 0.35:0.30:0 30:1. However, the components of silica ash, fly ash, mineral powder, etc. vary greatly, and the application guidance for commercial concrete in different regions is limited.
[0007] To this end, the present invention proposes a new method for preparing steam-cured concrete prefabricated components. Summary of the invention
[0008] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a method for preparing a steam-cured concrete prefabricated component, by pre-soaking recycled aggregate and slag sand and spraying them with Mg 2+ 、Al 3+ , Fe 3+ Inorganic salt solution or sodium dodecylbenzene sulfonate solution; a layer of cotton gauze pre-impregnated with silane coupling agent, nano-silicon dioxide, and nano-calcium carbonate solution is laid in every 20-50mm concrete, and then steam curing and carbonization curing are carried out to reduce the amount of calcium hydroxide formed as a hydration product and improve its morphology, thereby solving the problem of poor durability of precast concrete components prepared by steam curing and improving the later strength and durability of steam-cured concrete.
[0009] Technical solution: The present invention provides a method for preparing a steam-cured concrete prefabricated component, comprising the following steps: S1. Pre-soak the coarse and fine aggregates of concrete, take them out and dry them, and spray the surface of the coarse and fine aggregates of concrete after pre-soaking with Mg 2+ 、Al 3+ , Fe 3+ One or more of inorganic salt solutions, or sodium dodecylbenzene sulfonate solution; wherein, in the pre-soaking treatment, the pre-soaking solution is an aqueous solution or a sodium hydroxide solution; S2. Tie and fix several longitudinal steel bars in the concrete formwork; S3. Casting self-compacting concrete with coarse and fine aggregate obtained from S1, and paving pre-wet cotton gauze: paving a layer of pre-wet cotton gauze of the same size as the concrete formwork for every 20~50mm concrete; the pre-wet cotton gauze is fixed flat by the longitudinal reinforcement; S4 S3 obtained concrete steam curing; S5. The concrete obtained in S4 was demoulded and wet cured; S6. The concrete obtained in S5 is subjected to carbonization curing. The specific conditions of the carbonization curing are: CO2 concentration of 50~100%, carbonization pressure of 0.5~1.5MPa, curing temperature of 20~50℃, and curing time of 7h~24h.
[0010] Further, in S1, the mass concentration of the sodium hydroxide solution is 0.5-4%; In S1, the mass concentration of the inorganic salt solution is 0.01-2%; In S2, the mass concentration of the sodium dodecylbenzene sulfonate solution is 0.01-0.10%.
[0011] Furthermore, in S3, the pre-wetting solution for pre-wetting the cotton gauze comprises: 90-95% water, 1-5% silane coupling agent, 1-3% nano-silicon dioxide, and 0.5-2% nano-calcium carbonate.
[0012] Furthermore, in S1, among the coarse and fine aggregates of the concrete, the coarse aggregate is recycled aggregate, and the fine aggregate is slag sand.
[0013] Furthermore, the particle size of the concrete coarse aggregate is less than 10 mm.
[0014] Furthermore, in S3, the ratio of SiO2 / Al2O3 of the admixture in the self-compacting concrete is greater than 2.5.
[0015] Furthermore, in S3, 0.3-1.5 kg of fiber tubes are mixed into each cubic meter of the self-compacting concrete.
[0016] Furthermore, the fiber tube has a diameter of less than 1 mm and a length of 0.5-1.0 cm.
[0017] Preferably, in S5, the wet curing time is 6 h to 24 h.
[0018] Beneficial effects: Compared with the prior art, the specific beneficial effects of the present invention are as follows: 1. The present invention sets pre-wetted cotton gauze in the prefabricated component, which can restrain the swelling and deformation of concrete under steam curing conditions on the one hand, and on the other hand, the cotton gauze can absorb water, and can replenish water for the steam curing concrete when the steam curing concrete is dry inside. The cotton gauze sets an internal channel for the concrete, and the channel runs through the entire interior of the concrete through the fiber tube. The carbonization curing is accelerated by pressurization. CO2 gas can use the cotton gauze and the fiber tube as transmission channels, slowly enter the interior of the concrete in liquid form or gas form, and carbonize a large amount of calcium hydroxide formed under the steam curing conditions into calcium carbonate with fibrous, spherical, cubic and other morphologies, thereby increasing the strength of the concrete, filling and compacting the pores left by the cotton gauze and the fiber tube, and reducing the brittleness of the steam curing concrete.
[0019] 2. The coarse aggregate selected in the present invention is recycled concrete aggregate, and the fine aggregate is water slag sand, which has been soaked in water or alkaline solution. The active substances on the surface of the aggregate react with water, alkaline solution, etc. to form nano-state CSH and NASH, which increases the specific surface area of the aggregate. These substances will also act as crystal nuclei to promote the precipitation and generation of cement hydration product CSH around the aggregate, thereby improving the density of the interface transition zone. In addition, the soaked aggregate has a large specific surface area, and by spraying Mg-containing 2+ 、Al 3+ , Fe 3+ The inorganic salt solution or the sodium dodecylbenzene sulfonate solution can increase the adsorption of the above solution on the aggregate after soaking. At the same time, the above ions can consume calcium hydroxide to form hydrotalcite (Mg4Al2(OH) 14 · 3H2O), in addition, it can change the growth environment of calcium hydroxide crystals, affect the morphology of calcium hydroxide formation, and thus improve the mechanical properties of calcium hydroxide.
[0020] 3. By adjusting the ratio of SiO2 and Al2O3 in the mineral admixture and spraying Mg on the aggregate surface 2+ , so that more hydrotalcite is formed in the cement paste hardened under steam-curing conditions, and the Al2O3 content required to form hydrated garnet in the concrete is reduced, thereby controlling the amount of hydrated garnet (C3AH6) formed in the concrete under steam-curing conditions and reducing the shrinkage of the strength of the steam-cured concrete in the later stage.
[0021] 4. Pre-wetting and toughening the cotton gauze with a pre-wetting solution (water, silane coupling agent, nano-silicon dioxide, nano-calcium carbonate, etc.) can improve the bonding between the cotton gauze and cement concrete, increase the precipitation and formation of hydration products around the cotton gauze, and at the same time add nutrient solution to the concrete, reduce the formation of calcium hydroxide in steam-cured concrete, and improve the durability of steam-cured concrete. DETAILED DESCRIPTION
[0022] The present invention is described in detail below in conjunction with the embodiments.
[0023] It should be noted that the mineral admixtures used in the concrete of the present invention are mineral powder and silica fume, wherein the SiO2 content in the silica fume is 95%; the SiO2 content in the mineral powder is 35%, and the Al2O3 content is 20%.
[0024] Implementation 1: S1. Pre-soaking of concrete coarse and fine aggregates; wherein the concrete fine aggregate is water slag sand, and the pre-soaking solution is an aqueous solution; the concrete coarse aggregate is a recycled aggregate, and its maximum particle size is 10 mm, and the pre-soaking solution is a sodium hydroxide solution having a mass concentration of 0.5%; after soaking, take out and dry, and spray a magnesium nitrate solution having a mass concentration of 1% on the surface of the concrete coarse and fine aggregates after the pre-soaking treatment; S2. Tie and fix 4 longitudinal steel bars in the concrete formwork; S3. Cast self-compacting concrete with the coarse and fine aggregates of concrete pre-soaked in S1, and lay pre-wetted mesh cotton gauze: lay one layer of pre-wetted mesh cotton gauze of the same size as the concrete formwork for every 20 mm of concrete; the pre-wetted mesh cotton gauze is fixed and laid flat by longitudinal steel bars; the ratio of SiO2 / Al2O3 of the admixture in the self-compacting concrete is 5.67; in addition, each cubic meter of self-compacting concrete is also mixed with 0.3 kg of fiber tubes with a diameter of 0.01 mm and a length of 0.5 cm; the pre-wet solution of the pre-wetted cotton gauze is composed of: 95% water, 2% silane coupling agent, 2% nano-silicon dioxide, and 1% nano-calcium carbonate; S4. The concrete obtained in S3 is steam cured at a temperature of 60°C for 8h; S5. The concrete obtained in S4 was demoulded and cured in a saturated calcium hydroxide solution for 24h; S6. Carbonate the concrete obtained in S5, wherein the CO2 concentration of carbonation curing is 100%, the carbonation pressure is 0.5 MPa, the curing temperature is 50°C, and the curing time is 7 hours.
[0025] Implementation 2: S1. Pre-soaking of coarse and fine aggregates of concrete; wherein the coarse aggregate is recycled aggregate with a particle size of less than 10 mm, the fine aggregate is slag sand, and the pre-soaking solution of the coarse and fine aggregates of concrete is a sodium hydroxide solution having a mass concentration of 1%; after soaking, take out and dry, and spray a 0.05% aluminum sulfate solution on the surface of the coarse and fine aggregates of concrete after pre-soaking; S2. Tie and fix 5 longitudinal steel bars in the concrete formwork; S3. Cast self-compacting concrete with the coarse and fine aggregates of concrete pre-soaked in S1, and lay pre-wetted mesh cotton gauze: lay one layer of pre-wetted mesh cotton gauze of the same size as the concrete formwork for every 50mm of concrete; the pre-wetted mesh cotton gauze is fixed and laid flat by longitudinal steel bars; the ratio of SiO2 / Al2O3 of the admixture in the self-compacting concrete is 4.59; in addition, each cubic meter of self-compacting concrete is also mixed with 1.5kg of fiber tubes with a diameter of 0.05mm and a length of 0.7cm; the pre-wet solution of the pre-wetted cotton gauze is composed of: 90% water, 5% silane coupling agent, 3% nano-silicon dioxide, and 2% nano-calcium carbonate; S4. The concrete obtained in S3 is steam cured at a temperature of 60°C for 8h; S5. The concrete obtained in S4 is demoulded and then cured in water for 6 hours; S6. Carbonate the concrete obtained in S5, wherein the CO2 concentration of carbonation curing is 50%, the carbonation pressure is 1.5 MPa, the curing temperature is 50°C, and the curing time is 24 hours.
[0026] Implementation 3: S1. Pre-soaking of coarse and fine aggregates of concrete; wherein the coarse aggregate is recycled aggregate with a particle size of less than 10 mm, the fine aggregate is slag sand, and the pre-soaking solution of the coarse and fine aggregates of concrete is a 4% sodium hydroxide solution by mass concentration; after soaking, take out and dry, and spray a 2% iron sulfate solution on the surface of the coarse and fine aggregates of concrete after pre-soaking; S2. Tie and fix 4 longitudinal reinforcement bars in the concrete formwork; S3. Use the coarse and fine aggregates of concrete pre-soaked in S1 to cast self-compacting concrete, and lay pre-wetted mesh cotton gauze: lay one layer of pre-wetted mesh cotton gauze of the same size as the concrete formwork for every 30 mm of concrete; the pre-wetted cotton gauze is fixed and laid flat by longitudinal steel bars; the ratio of SiO2 / Al2O3 of the admixture in the self-compacting concrete is 3.71; in addition, each cubic meter of self-compacting concrete is also mixed with 1.0 kg of fiber tubes with a diameter of 0.08 mm and a length of 1 cm; the pre-wet solution of the pre-wetted cotton gauze is composed of: 93% water, 5% silane coupling agent, 1% nano-silicon dioxide, and 1% nano-calcium carbonate; S4. The concrete obtained in S3 is steam cured at a temperature of 60°C for 8h; S5. The concrete obtained in S4 was demoulded and cured in a saturated calcium hydroxide solution for 24h; S6. Carbonate the concrete obtained in S5, wherein the CO2 concentration of carbonation curing is 70%, the carbonation pressure is 1.0 MPa, the curing temperature is 50°C, and the curing time is 8 hours.
[0027] Implementation 4: S1. Pre-soaking of coarse and fine aggregates of concrete; wherein the coarse aggregate is recycled aggregate with a particle size of less than 10 mm, the fine aggregate is slag sand, and the pre-soaking solution of the coarse and fine aggregates of concrete is a sodium hydroxide solution with a mass concentration of 2%; after soaking, take out and dry, and spray a 0.05% sodium dodecylbenzene sulfonate solution on the surface of the coarse and fine aggregates of concrete after pre-soaking; S2. Tie and fix 5 longitudinal steel bars in the concrete formwork; S3. Use the coarse and fine aggregates of concrete pre-soaked in S1 to cast self-compacting concrete, and lay pre-wetted mesh cotton gauze: lay one layer of pre-wetted mesh cotton gauze of the same size as the concrete formwork for every 20 mm of concrete; the pre-wetted cotton gauze is fixed and laid flat by longitudinal steel bars; the ratio of SiO2 / Al2O3 of the admixture in the self-compacting concrete is 3.33; in addition, each cubic meter of self-compacting concrete is also mixed with 1.0 kg of fiber tubes with a diameter of 0.05 mm and a length of 1 cm; the pre-wet solution of the pre-wetted cotton gauze is composed of: 90% water, 5% silane coupling agent, 3% nano-silicon dioxide, and 2% nano-calcium carbonate; S4. The concrete obtained in S3 is steam cured at a temperature of 60°C for 8h; S5. The concrete obtained in S4 was demoulded and wet-cured with a saturated calcium hydroxide solution for 24 hours; S6. Carbonate the concrete obtained in S5, wherein the CO2 concentration of carbonation curing is 70%, the carbonation pressure is 0.5 MPa, the curing temperature is 20°C, and the curing time is 7h.
[0028] Performance testing:
[0029] The mix ratio of comparative concrete is: cement: 300kg, mineral powder: 120kg, natural sand: 810kg, gravel: 1100kg, water: 160kg, water reducing agent: 6kg, steam curing condition is 80℃, and curing time is 8 hours.
[0030] Table 2 is the performance evaluation index of the present invention. This index is based on the compressive strength and sulfate corrosion resistance of the concrete prepared in Implementation Examples 1 to 4 and the comparative example. The test method refers to GB50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" and GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The test results are shown in Table 2. The curing of the mechanical properties samples of the embodiment is to continue standard curing (temperature is 20±2°C, humidity>95%) for 3d or 90d after completing the curing of the present invention. The curing conditions of the mechanical properties samples of the comparative example are standard curing.
[0031]
[0032] It can be seen from Table 2 that the 3d strength of the steam-cured concrete precast components prepared by the present invention is basically at the same strength level as that of the comparative example, with a small difference. However, the strength growth rate of the concrete prepared by the present invention at 90d is significantly higher than that of the comparative example, and the sulfate corrosion resistance of the concrete of the present invention is significantly higher than that of the comparative example.
[0033] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a steam-cured concrete prefabricated component, characterized in that: The following steps are involved: S1. Pre-soak the coarse and fine aggregates of concrete, take them out and dry them, and spray Mg-containing 2+ 、Al 3+ , Fe 3+ One or more of inorganic salt solutions, or sodium dodecylbenzene sulfonate solution; wherein, in the pre-soaking treatment, the pre-soaking solution is an aqueous solution or a sodium hydroxide solution; S2. Tie and fix several longitudinal steel bars in the concrete formwork; S3. Casting self-compacting concrete with coarse and fine aggregate obtained from S1, and paving pre-wet cotton gauze: paving a layer of pre-wet cotton gauze of the same size as the concrete formwork for every 20~50mm concrete; the pre-wet cotton gauze is fixed flat by the longitudinal reinforcement; S4 S3 obtained concrete steam curing; S5. The concrete obtained in S4 was demoulded and wet cured; S6. Carbonation curing is performed on the concrete obtained in S5; the specific conditions of the carbonation curing are: CO2 concentration of 50~100%, carbonation pressure of 0.5~1.5MPa, curing temperature of 20~50℃, and curing time of 7h~24h.
2. The method for preparing a steam-cured concrete prefabricated component according to claim 1, characterized in that: In S1, the mass concentration of the sodium hydroxide solution is 0.5-4%; In S1, the mass concentration of the inorganic salt solution is 0.01-2%; In S2, the mass concentration of the sodium dodecylbenzene sulfonate solution is 0.01-0.10%.
3. The method for preparing a steam-cured concrete prefabricated component according to claim 1, characterized in that: In S1, among the coarse and fine aggregates of the concrete, the coarse aggregate is recycled aggregate and the fine aggregate is slag sand.
4. The method for preparing a steam-cured concrete prefabricated component according to claim 3, characterized in that: The coarse aggregate has a particle size of less than 10 mm.
5. The method for preparing a steam-cured concrete prefabricated component according to claim 1, characterized in that: In S3, the pre-wetting solution for pre-wetting the cotton gauze is composed of: 90-95% water, 1-5% silane coupling agent, 1-3% nano silicon dioxide, and 0.5-2% nano calcium carbonate.
6. The method for preparing a steam-cured concrete prefabricated component according to claim 1, characterized in that: In S3, the ratio of SiO2 / Al2O3 of the admixture in the self-compacting concrete is greater than 2.
5.
7. The method for preparing a steam-cured concrete prefabricated component according to claim 1, characterized in that: In S3, 0.3~1.5kg of fiber tubes are also mixed into each cubic meter of self-compacting concrete.
8. The method for preparing a steam-cured concrete prefabricated component according to claim 7, characterized in that: The fiber tube has a diameter of less than 1 mm and a length of 0.5 to 1.0 cm.
9. The method for preparing a steam-cured concrete prefabricated component according to claim 1, characterized in that: In S5, the wet curing time is 6h~24h.
Citation Information
Patent Citations
Additive capable of improving durability of steam-cured concrete, and concrete coarse aggregate treated thereby
CN102849976B
Special high-activity composite admixture for steam-cured concrete product
CN105218051A
Steam-cured concrete and preparation method thereof
CN114057445A
A method for preparing precast concrete components
CN114474359B